2004
DOI: 10.2136/sssaj2004.1145
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Clay Content, Clay Type, and Shrinkage Properties of Soil Samples

Abstract: of shrinkage curves on undisturbed core samples allowed improvement of the knowledge of soil shrinking behav-The availability of methods for quasi-continuous measurements of ior, and to develop shrinkage curve models with differsoil shrinkage curves allowed the development of new models. The ent sets of parameters, as reviewed in Braudeau et al. exponential (XP) model allows the calculation of the volume of two pore phases in the soil, namely macro and micropore volumes. The (1999). micropore volume is identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
133
2
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 20 publications
13
133
2
6
Order By: Relevance
“…It was reported in Rahman (2000) that 'The smectite mineral particles have a large specific surface area of up to 800 m 2 g -1 and have a high adsorptive capacity and can be compacted to give very low hydraulic conductivity (10 -11 to 10 -13 ms -1 )'. Boivin et al (2004) reported that swelling capacity of the soil increases with clay content, which is related to clay type, pore size, and moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported in Rahman (2000) that 'The smectite mineral particles have a large specific surface area of up to 800 m 2 g -1 and have a high adsorptive capacity and can be compacted to give very low hydraulic conductivity (10 -11 to 10 -13 ms -1 )'. Boivin et al (2004) reported that swelling capacity of the soil increases with clay content, which is related to clay type, pore size, and moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…The reconstituted Rodah soil samples [AM67, AM68, and AM69] had almost an S-shape for the SSCs (Figure 6A) with steep slopes of the basic shrinkage phases of the shrinkage curves. Sshape usually indicates a good soil structure (Braudeau et al, 1999;Boivin et al, 2004;Horn, 2005, 2013) and these samples were constructed from macro-aggregates (200 μm-2 mm) excluding all the fine sand and loose silt particles less than 200 μm. Figure 6A shows a very good match of the measured WRC and SSC for the three replicates.…”
Section: The Measured Water Retention and Soil Shrinkage Curvesmentioning
confidence: 99%
“…While, in the rubber balloon method, reconstituted soil cores were used in most studies (Tariq and Durnford, 1993a;Cornelis et al, 2006). In this approach, the soil samples were submerged into water and then the change in the sample volume was determined from the volume of displaced fluid; (ii) physical measurement-based approach: where the soil cores "disturbed or undisturbed" dimensions were measured directly using a vernier caliper (Berndt and Coughlan, 1977;Huang et al, 2011), a linear displacement transducer (Boivin et al, 2004;Braudeau and Mohtar, 2004) or a thin metal stick (Kim et al, 1992); (iii) laser sensors-based approach: where the soil core diameter and height were determined through laser beams such as the retractometer apparatus (Braudeau et al, 1999), (iv) imagebased approach: where the volume of the soil sample (either clod or core) was either scanned with a 3-D optical scanner (Sander and Gerke, 2007) or by a simple standard digital camera (Stewart et al, 2012). Several studies have discussed and compared these methods, Cornelis et al (2006) showed that there were significant differences between the Archimedes' principlebased methods "paraffin-coated and rubber balloon methods" and the physical measurement-based methods "vernier caliper method" where the former produced more accurate and reliable data; however, Sander and Gerke (2007) observed some errors in the resin-coated method that affects the measured volume due to inadequate coating or penetration of the coating materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cette zone située entre 40 et 60 cm apparaît bien dans le modèle, mais on ne lui a pas conféré de propriétés particulières. De plus, la porosité structurale des Hollaldés va être fortement réduite lorsque la teneur en eau du sol augmente, en raison des phénomènes de gonflement (BOIVIN et al 2004;2006). Ces observations montrent qu'il faut considérer les estimations des flux par modélisation sur les Hollaldés avec prudence, en tout cas avec plus de prudence que sur les Fondés.…”
Section: Confrontation Des Hypothèses Et Des Résultats De La Modélisaunclassified